POTENSI INDUSTRI PARIWISATA KABUPATEN BANYUMAS - Sri Hermawati; Yusye Milawaty (Universitas Gunadarma, 2017)
According to the plan of development of creative industries in Indonesia until 2025 the tourism industry is expected to be one of the drivers of economic growth through creative industry. This study aims to describe the development of the tourism industry and economic activity associated with the industry in the area of Banyumas. The data used are the rate of occupancy hotels , long stay travelers, the number of tourists, the number of hospitality workers and GDP for the period 2003 to 2011. A survey of the economic actors was done to determine the economic activity around the existing tourism industry. Banyumas tourism industry still relies on nature tourism. Some tourism object are there in desperate need of attention because of the condition that local governments are not maintained resulting in lower interest visitors. Some distinctive cultural can still be developed because it has its own characteristics that absorb the influences of two differences culture. The mixing of natural tourism and cultural tourism can increase the economic potential of the community.Keywords: tourism, nature tourism, creative industries